Speciation of Ions in Groundwater and its Applications - Prasanna, Mohan Viswanathan (I.K. International Publishing House Pvt. Ltd, 2010)
Speciation of ions in groundwater is very important to understand its hydrogeochemical evolutions from its origin to its present status. The speciation will help to understand the geochemical process which controls their evolution and their present day environmental conditions which will ultimately lead us to utilize them directly or after the required treatment process to make them safe and useable. Some of the ions and their speciation were discussed in this line in this chapter.